The Role of Openness in the Effect of ICT on Governance - Simplice Asongu; Jacinta C. Nwachukwu (African Governance and Development Institute (AGDI), 2017)
The study investigates how openness influences information and communication technology (ICT) penetration for improved government quality in sub-Saharan Africa for the period 2000-2012. Openness is measured in terms of trade and financial globalisation whereas ICT is proxied with mobile phone and internet penetration rates. Ten bundled and unbundled governance indicators are used. The empirical evidence is based on Generalised Method of Moments with forward orthogonal deviations. The main findings are: First, financial openness has an edge over trade openness when combined with ICT to affect both economic and institutional governance. Second, mobile phones have an edge over internet penetration in complementing (i) trade openness for economic governance and (ii) financial openness for institutional governance. Third, net effects on political governance are consistently negative. Taken together, in the short-run, openness-driven ICT policies are more rewarding in terms of economic and institutional governance than political governance. Fourth, catch-up in governance is facilitated by the interaction between openness and ICT. Contributions of these findings to literature are discussed.
Keywords: F40; O38; O40; O55; P37; 330; Openness; ICT; Governance; Africa